International Jurisdiction on Fighting Against Corruption - E. T. Mayboroda (Теоретическая и прикладная юриспруденция)
The urgency of the article is stipulated by the importance to form international legal institutes aiming at fighting against corruption and the problem related to implementing international regulations of the anti-corruption purposefulness in national legal systems. The use of formal legal methods allowed to research the following groups of the most important anti-corruption regulators: international anti-corruption standards and principles, international and legal mechanisms of monitoring the fulfillment of anti-corruption conventions, and international legal measures to prevent corruption. Empiric data show that the lack of the system counteraction to corruption as a negative social and legal phenomenon causes the erosion of legal institutes, and finally, their full non-operability. It is necessary to further integrate international cooperation in this area. It must result in the formation of the standard unanimity of institutes of national jurisdiction in fighting against corruption.